The Funk of White Souls: Toward a Du Boisian Theory of the White Church. (29th May 2022) - Mayrl, Damon
Abstract: This article revisits the writings of W.E.B. Du Bois on the white church. Drawing on a synthetic reading of his scholarship on white Christianity, I argue that Du Bois conceives of the white church as a racialized organization that has been indelibly shaped by white supremacy. I then elaborate six mechanisms identified by Du Bois through which white churches further perpetuate white supremacy: legitimation, revisionism, inaction, segregation, missionary work, and charitable giving. Building on this analysis, I sketch a Du Boisian agenda for research on the white church and show how it can enrich scholarship in the sociology of religion, critical scholarship on race, and the Du Boisian renaissance more broadly.